Entre risos e rusgas: o conflito político-teatral entre padre Marcelino e cônego Januário (1831-1836) - Guasti, Victor Augusto Mendonça (2023)
Between 1831 and 1836, the initial years of the Brazilian Regency Period, there were several revolts and seditions in the court, as a result of the various political and economic dissatisfactions that the population harbored. Among these conflicts occurred the Sedition of Praia Grande (1834) under the leadership of Father Marcelino Pinto Ribeiro Duarte (1788- 1860). Once arrested, Marcelino was attacked by Canon Januário da Cunha Barbosa (1780- 1846), who wrote a theatrical satire mocking the priest. Once acquitted and free, Marcellin responded to the Canon by writing a theatrical farce. This study aims to understand, reconstitute and present the political-journalistic-theatrical battle waged between the priests, as well as the repercussions it had in the press of the period. It is intended, in this sense, to identify the political ideas defended by each of the researched clerics, and how these contributed to the occurrence of the quarrel. This investigation has theatrical plays and the press as its main documentary corpus, considering that newspapers were privileged spaces for the political debate of the period and for the dissemination and discussion of theatrical life in Rio de Janeiro. For the analysis of the documentation, this research uses the study of political languages, proposing the identification of the most used words in the plays and newspapers written by the priests, as well as the analysis of the composition of a new language, composed of resignifications resulting from the political dynamics of the new moment inaugurated by the abdication of Dom Pedro I (1831). In addition to the study of languages, this study uses the concept of political culture, aiming to identify new values and symbols that are inserted in imperial society during the vacancy of the throne. Based on the cited theoretical-methodological premises, the hypothesis is supported that the disagreements between Father Marcelino and Canon Januário reflected the political disputes between the group that defended the centralization of the Empire and the faction that advocated the federalization of the monarchy, whose apex occurred in the same period as the conflict between the priests.